The Structural Assessment of Glycosylation Sites Database - SAGS – An Overall View on N-Glycosylation - Surleac, Marius D.; Spiridon, Laurentiu N.; Tacutu, Robi; Milac, Adina L; Petrescu, Stefana M.; Petrescu, Andrei-J (IntechOpen, 2012)
None